2018
DOI: 10.1115/1.4038323
|View full text |Cite
|
Sign up to set email alerts
|

Variable Geometry Compressors for Heavy Duty Truck Engine Turbochargers

Abstract: This paper presents the development approach, design, and evaluation of three turbocharger compressors with variable geometry for heavy duty engines. The main goal is the improvement of fuel economy without sacrifices regarding any other performance criteria. In a first step, a vaned diffuser parameter study shows that efficiency improvements in the relevant operating areas are possible at the cost of reduced map width. Concluding from the results, three variable geometries with varying complexity based on van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They showed that a reduction in the leading edge angle results in a shift of the compressor operating range towards lower mass flow rates. By implementing an actuation mechanism, which allows the flexible pivoting of the diffuser vanes, the operating range of the compressor can be adjusted depending on the operating conditions [13,14]. However, gaps between end walls and diffuser vanes, which are necessary for a flexible pivoting concept, cause aerodynamic losses and thus reduce efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that a reduction in the leading edge angle results in a shift of the compressor operating range towards lower mass flow rates. By implementing an actuation mechanism, which allows the flexible pivoting of the diffuser vanes, the operating range of the compressor can be adjusted depending on the operating conditions [13,14]. However, gaps between end walls and diffuser vanes, which are necessary for a flexible pivoting concept, cause aerodynamic losses and thus reduce efficiency.…”
Section: Introductionmentioning
confidence: 99%